Effect of Benidipine Hydrochloride, a Long-acting T-type Calcium Channel Blocker, on Blood Pressure and Renal Function in Hypertensive Patients with Diabetes mellitus - Seino, Hiroaki; Miyaguchi, Shuichi; Yamazaki, Toshiro; Ota, Setsu; Yabe, Ryuji; Suzuki, Susumu (Arzneimittelforschung, 2007)
Background: Calcium channel blockers are commonly used to treat hypertension, and are known to generally act on the L-type calcium channel. Recent studies have shown, however, that some calcium channel blockers also block other calcium channel subtypes, including N- and T-type channels. Cilnidipine (CAS 132203-70-4) is an L- and N-type calcium channel blocker, and benidipine hydrochloride (benidipine, CAS 91599-74-5) is known to inhibit the T-type as well as L- and N-type calcium channels. In this study, effects of switching from cilnidipine to benidipine on blood pressure (BP) lowering and renal functions were investigated in order to clarify the physiological properties of the T-type calcium channel.Methods and results: Forty hypertensive patients with diabetes and poor BP control despite receiving cilnidipine were selected, and the changes in BP and urine protein (UP) scores were investigated retrospectively after switching from cilnidipine to benidipine for more than 3 months. BP (systolic/diastolic) significantly decreased from 155.8 ± 13.7 mmHg/76.5 ± 13.3 mmHg to 145.9 ± 17.0 mmHg/71.4 ± 13.7 mmHg after benidipine treatment, and this effect was stably maintained for one year. UP also significantly decreased from 1.29 to 0.67 in the mean score. The decrease in UP may be explained by a mechanism other than BP lowering effect.Conclusion: These results demonstrate that benidipine has a more potent anti-hypertensive effect than cilnidipine and also a renoprotective effect, indicating the high usefulness of benidipine in hypertensive patients with diabetes. T-type calcium channel blockade was suggested to be possibly involved in the enoprotective effect of benidipine.
Keywords: Benidipine hydrochloride, antihypertensive effect, renoprotective effect; Calcium channel blockers, T-type calcium channel; CAS 91599-74-5; CAS 132203-70-4; Coniel®; Diabetes mellitus, hypertensive patients; Hypertension, patients with diabetes mellitus